Perancangan Troli untuk Meningkatkan Efisiensi Pemindahan Bahan Baku dengan Pendekatan Ergonomis pada UMKM Kerupuk Mawar - Naufal Irsyaad Arafah; Siti Mundari (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Material handling activities at UMKM Kerupuk Mawar are still carried out semi-manually, resulting in poor ergonomic working postures and potentially causing Musculoskeletal Disorders (MSDs). This study aims to design an ergonomic trolley to improve the efficiency of raw material movement and reduce workers' physical workload. The methods used were Rapid Entire Body Assessment (REBA) to evaluate work posture risks and an anthropometric approach to determine the trolley dimensions. The results showed that the ergonomic trolley design has a handle height of 107 cm and a handle diameter of 5 cm based on workers' anthropometric data. The implementation of the ergonomic trolley reduced the REBA score for loading activities from 4 to 3 and raw material lifting activities from 8 to 2. Furthermore, the material handling time decreased from 81.80 seconds to 60.75 seconds, the carrying capacity increased from 2 to 4 sacks, and the handling frequency decreased from 15 to 8 cycles